PERAWATAN SALURAN AKAR VITAL PADA GIGI INCISIVUS LATERAL MAXILLA PULPITIS IRREVERSIBLE (Laporan Kasus) - Cahyani Cahyani; Dessy Rahmahwati (Muhammadiyah University Press, 2022)
Irreversible pulpitis is a persistent inflammatory condition of the pulp, which can be symptomatic or asymptomatic caused by a nerve stimulus. Tooth with pulp inflammation need root canal treatment to remove irritants of bacteria and clean the infected root canal from necrotic tissue. Root canal treatment aims to keep the teeth functioning properly. Irreversible pulpitis symptomps include persistent spontaneous pain of an external cause. The stages of root canal treatment include: root canal instrumentation which includes cleaning and shaping (biomechanical), disinfection, and obturation. A 16-year-old woman came to RSGM Soelastri, University of Muhammadiyah Surakarta with a complaint of a damaged restoration on her anterior teeth. Intra-oral examination revealed that tooth 12 appeared to be a damaged restoration. sondation (+), percussion (-), palpation (-), vitality test (+), EPT: 34, and Oral Hygiene 1,2 (moderate). The diagnosis for this case irreversible pulpitis with multivisit vital root canal treatment. The purpose of this case report irreversible pulpitis, root canal treatment, vitalis to describe of an endodontic treatment procedure that can maintain tooth 12. The control was carried out 1 week after treatment and patient did not feel any complaints. Intraoral examination were. sondation (-), percussion (-), palpation (-), vitality test (-) treatment was successfully carried out and proceed with final restoration of a porcelain fused to metal jacket crown with fiber post.Keywords: